2015
DOI: 10.1007/s00170-015-7198-8
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on microstructure and properties of Inconel 52M overlays deposited by laser beam and GTA cladding

Abstract: The current study investigates the overlays deposited by laser beam (LB) and gas tungsten arc (GTA) cladding with Inconel 52M filler wire in nuclear power plants. The effects of the deposition methods on the cross section profile, microstructures, and mechanical properties of both overlays are studied using optical microscope, scanning electron microscope (SEM), tensile and impact test and microhardness measurements. Experimental results show that LB cladding with higher wire feed rate improves the deposition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…3 shows SEM image of the as-weld Alloy ENiCrFe-7 and the heat treatment one after 615℃/48h, it is found that Alloy ENiCrFe-7 consists of dendrite(No.1), interdendrite(No.2), spherical precipitates(No.3) in the dendrites and irregular precipitates(No.4) in the interdendrites. It is revealed from Table .3 that Nb content of interdendrites is higher than that of dendrite, it is caused by constitutional supercooling and the equilibrium partition coe cient K of Nb is less than 1 [21] , it is also found that the precipitates are (Al,Ti,O)-rich in the dendrite and (Nb,C)-rich in the interdendritic region simultaneously. There are not precipitates at the grain boundary of the as-weld alloy ENiCrFe-7, while heat treatment one after 48h have continuous precipitates along the grain boundary.…”
Section: Resultsmentioning
confidence: 97%
“…3 shows SEM image of the as-weld Alloy ENiCrFe-7 and the heat treatment one after 615℃/48h, it is found that Alloy ENiCrFe-7 consists of dendrite(No.1), interdendrite(No.2), spherical precipitates(No.3) in the dendrites and irregular precipitates(No.4) in the interdendrites. It is revealed from Table .3 that Nb content of interdendrites is higher than that of dendrite, it is caused by constitutional supercooling and the equilibrium partition coe cient K of Nb is less than 1 [21] , it is also found that the precipitates are (Al,Ti,O)-rich in the dendrite and (Nb,C)-rich in the interdendritic region simultaneously. There are not precipitates at the grain boundary of the as-weld alloy ENiCrFe-7, while heat treatment one after 48h have continuous precipitates along the grain boundary.…”
Section: Resultsmentioning
confidence: 97%
“…An alternative to applying a weld overlay onto the damaged components is performed instead of replacement [5]. IN52, 52M, and 152 alloys are widely used as the filler metals for the overlay-welding of different components to alleviate SCC damage in those dissimilar welds [6,7]. Induced compressive residual stress in the inner surface of the pipes is helpful to lower the SCC sensitivity after overlay-welding [8,9].…”
Section: Introductionmentioning
confidence: 99%